Black helicopters - Kiernan, Caitlín R. (Kiernan, Caitlín R. Tinfoil dossier, 2018)
A dark jewel of a novella, this definitive edition of Caitlín R. Kiernans Black Helicopters is the expanded and completed version of the World Fantasy Award-nominated original. Just as the Signalman stood and faced the void in Agents of Dreamland, so it falls to Ptolema, a chess piece in her agencys world-spanning game, to unravel what has become tangled and unknowable. Something strange is happening on the shores of New England. Something stranger still is happening to the world itself, chaos unleashed, rational explanation slipped loose from the moorings of the known. Two rival agencies stare across the Void at one another. Two sisters, the deadly, sickened products of experiments going back decades, desperately evade their hunters. An invisible war rages at the fringes of our world, with unimaginable consequences and Lovecraftian horrors that ripple centuries into the future.